Advocacy for Muslim women and children as victims of domestic violence in Central Java, Indonesia - Ulinnuha, Muhammad; Widiyanto, Asfa (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
This study is aimed at revealing the strategies of advocacy for Muslim women and children who become victims of domestic violence in Semarang, Central Java, Indonesia. This research was conducted at the ‘Legal Resources Centre for Gender Justice and Human Rights’ (LRC KJHAM) and the ‘Regional Technical Implementation Unit for the Protection of Women and Children’ (UPTD PPA). Data collection techniques include in-depth interviews and documentation. It employs two main theories, namely conflict theory and the maqasid al-shari’a (objectives of Islamic law). The results show that the advocacy efforts embrace complaint services, assessment, medical referrals, provision of safe houses, counselling, litigation and non-litigation legal assistance, empowerment, and policy advocacy. Based on conflict theory, a dialectic is found in domestic violence cases. This can be observed that male dominance in a patriarchal system represents a thesis, whilst rejection of violence as a violation of human rights and Islamic principles embodies an antithesis, and advocacy as a form of resolution serves as synthesis. Furthermore, from the perspective of maqasid al-shari’a, this advocacy aligns with the five essential objectives of Islamic law, namely, preservation of religion (ḥifẓ al-dīn) through strengthening faith; preservation of life (ḥifẓ al-nafs) through medical services and safe houses; preservation of lineage (ḥifẓ al-naśl) through child protection and legal aid; preservation of intellect (ḥifẓ al-‘aql) through counselling; and preservation of wealth (ḥifẓ al-māl) through economic empowerment. This paper argues that the advocacy provided in these two institutions is not merely legal-formal, but also reflects a broader effort for social transformation rooted in Islamic teachings.